The Influence of Prices on The Interest of Buying Consumers of Yamaha Motorcycles in PT. Ramarayo Sumdeang Branch - Sifa Unazah Badriah; Gustina Hidayat; Rani Munggaran (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2022)
The Influence of Price On Consumer Buying Interest Yamaha Motorcycles At PT. Ramarayo Branch Sumedang. This research aims to know the pricing and buying interest of consumers and to know the influence of prices on the buying interest of yamaha motorcycle consumers in PT. Ramarayo Branch Sumedang. The analytical techniques used are simple regression analysis, product moment correlation test, determination coefficient and hypothesis test. The relationship between Price and Consumer Buying Interest yamaha motorcycles at PT. Ramarayo Sumedang branch is 0.645 and there is at intervals of 0.60-0.799 or it can be said that the price relationship with consumer buying interest in PT. Ramarayo Branch sumedang has a strong relationship. Price Influence on Consumer Buying Interest yamaha motorcycles on PT. Ramarayo Sumedang branch by 41%, or the influence of Price 41% on Consumer Buying Interest. Hypothesis that there is a positive influence between Price and Consumer Buying Interest yamaha motorcycles on PT. Ramarayo Branch Sumedang and can be accepted with thitung > ttabel or 7416 > 1,661.